2014
DOI: 10.1371/journal.pone.0098048
|View full text |Cite
|
Sign up to set email alerts
|

Oral Vaccination with Heat Inactivated Mycobacterium bovis Activates the Complement System to Protect against Tuberculosis

Abstract: Tuberculosis (TB) remains a pandemic affecting billions of people worldwide, thus stressing the need for new vaccines. Defining the correlates of vaccine protection is essential to achieve this goal. In this study, we used the wild boar model for mycobacterial infection and TB to characterize the protective mechanisms elicited by a new heat inactivated Mycobacterium bovis vaccine (IV). Oral vaccination with the IV resulted in significantly lower culture and lesion scores, particularly in the thorax, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 59 publications
9
68
0
1
Order By: Relevance
“…This suggests a new mechanism of immune protection by which low-intensity priming enhances early phagocytic responses independently of humoral and cellular adaptive immune responses for, at least, six months. This mechanism would support the empirical evidence of protection induced by killed mycobacterial vaccines [3,4,5]. These findings fit well with the recently proposed general concept of trained immunity, which was developed to explain the observation that innate immune responses provide unspecific protection against pathogens including other than those that originally triggered the immune response.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…This suggests a new mechanism of immune protection by which low-intensity priming enhances early phagocytic responses independently of humoral and cellular adaptive immune responses for, at least, six months. This mechanism would support the empirical evidence of protection induced by killed mycobacterial vaccines [3,4,5]. These findings fit well with the recently proposed general concept of trained immunity, which was developed to explain the observation that innate immune responses provide unspecific protection against pathogens including other than those that originally triggered the immune response.…”
Section: Introductionsupporting
confidence: 82%
“…The blood samples were analysed using an in-house anti- M . bovis ELISA with bovine PPD as the antigen [5]. This assay includes a serum Mycobacterium phlei pre-absorption step to reduce non-specific reactivity caused by environmental mycobacteria.…”
Section: Methodsmentioning
confidence: 99%
“…In general terms, the pigs showed more severe lesions after challenge with field M. bovis than wild boar challenged with similar doses in previous trials (17,35,36). Also, abdominal lesions were more evident in pigs.…”
Section: Discussionmentioning
confidence: 63%
“…It has been found that oral immunization with a new heat inactivated Mycobacterium bovis vaccine protects in terms of culture and lesion scores, particularly in the respiratory tract. These findings make this model a promising tool for reaching the goal of preventing TB pulmonary disease [80]. Mechanisms that correlated with these effects were associated with humoral responses, the complement component C3 and inflammasome.…”
Section: Expert Commentarymentioning
confidence: 80%